Bacterial Nanocellulose in Dentistry: Perspectives and Challenges - Oliveira Barud, Helida Gomes de; Silva, Robson Rosa da; Borges, Marco Antonio Costa; Castro, Guillermo Raul; Ribeiro, Sidney Jose Lima [UNESP]; Silva Barud, Hernane da (Mdpi, 2021)
Bacterial cellulose (BC) is a natural polymer that has fascinating attributes, such as biocompatibility, low cost, and ease of processing, being considered a very interesting biomaterial due to its options for moldability and combination. Thus, BC-based compounds (for example, BC/collagen, BC/gelatin, BC/fibroin, BC/chitosan, etc.) have improved properties and/or functionality, allowing for various biomedical applications, such as artificial blood vessels and microvessels, artificial skin, and wounds dressing among others. Despite the wide applicability in biomedicine and tissue engineering, there is a lack of updated scientific reports on applications related to dentistry, since BC has great potential for this. It has been used mainly in the regeneration of periodontal tissue, surgical dressings, intraoral wounds, and also in the regeneration of pulp tissue. This review describes the properties and advantages of some BC studies focused on dental and oral applications, including the design of implants, scaffolds, and wound-dressing materials, as well as carriers for drug delivery in dentistry. Aligned to the current trends and biotechnology evolutions, BC-based nanocomposites offer a great field to be explored and other novel features can be expected in relation to oral and bone tissue repair in the near future.
Keywords: bacterial cellulose; biomaterials; nanocomposites; tissue engineering; guided tissue regeneration